A critical review of the current evidence examining whether resistance training improves time trial performance. Issue 13 (3rd July 2018) - Dankel, Scott J.; Mattocks, Kevin T.; Mouser, J. Grant; Buckner, Samuel L.; Jessee, Matthew B.; Loenneke, Jeremy P.
ABSTRACT: A number of reviews have concluded that resistance training is beneficial for improving sports performance despite the inclusion of studies which do not actually measure a performance outcome (i.e. a timed trial). The purpose of this review was to examine only those studies which would allow us to infer the benefits of resistance training on improving time trial performance. Of the nine studies meeting all inclusion criteria only three demonstrated an additive effect of adding resistance training to the current activity-specific training being performed. These three studies demonstrated improvements in either 5 or 10 km time trial among recreationally skilled athletes (i.e. non-elite level time). Previous reviews have included studies which did not include: (1) performance outcomes; (2) control groups; and/or (3) equal volumes of activity-specific exercise among the resistance training and control groups. Presently, there is little evidence that adding resistance exercise to a sport-specific training program will augment time trial performance. While it is difficult to perform such long-term studies assessing the effects of resistance training among time trial athletes, the statement that resistance training is efficacious for improving time trial performance should be tempered until sufficient evidence is presented to support such claims.